A new approach for measurement of the low-temperature specific heat capacity. (15th November 2022) - Jiao, Y.; Liu, C.F.; Cui, X.P.; Zhang, J.; Huang, L.J.; Geng, L.
Highlights: Three ways were proposed to measure the low-temperature constant pressure specific heat capacity by synchronous thermal analyzer. Creating low-temperature environment before measurement can bring temperature stability and improve measurement accuracy. The measurement error was greatly decreased with increasing temperature to above room-temperature. Abstract: The manuscript presented the application of simultaneous thermal analyzer (STA449F3) at low-temperature Differential Scanning Calorimetry (DSC) and specific heat capacity tests. Moreover, some problems were found during the specific heat capacity measurement. The STA449F3 instrument can provide accurate characteristic temperature and enthalpy values calculation. However, the specific heat capacity deviation increased gradually when temperature increased above room-temperature. The liquid nitrogen cooling way led to nonlinear change of temperature with time during increasing, decreasing and holding temperature process, and larger deviation of low-temperature specific heat capacity. Three ways were adopted to measure the specific heat capacity from below zero to above room-temperature. The error between the studied and reference values was greatly reduced via creating a non-liquid nitrogen cooling environment.